In situ monitoring of the charge carrier dynamics of CH3NH3PbI3 perovskite crystallization process. Issue 39 (23rd September 2019) - Serpetzoglou, Efthymis; Konidakis, Ioannis; Maksudov, Temur; Panagiotopoulos, Apostolos; Kymakis, Emmanuel; Stratakis, Emmanuel
Abstract : Although CH3 NH3 PbI3 perovskite has attracted enormous scientific attention over the last decade or so, important information on the charge extraction dynamics and recombination processes in perovskite devices is still missing. Abstract : Although methylammonium lead iodide (CH3 NH3 PbI3 ) perovskite has attracted enormous scientific attention over the last decade or so, important information on the charge extraction dynamics and recombination processes in perovskite devices is still missing. Herein we present a novel approach to evaluate the quality of CH3 NH3 PbI3 layers, via in situ monitoring of the perovskite layer charge carrier dynamics during the thermal annealing crystallization process, by means of time-resolved femtosecond transient absorption spectroscopy (TAS). In particular, CH3 NH3 PbI3 films were deposited on two types of polymeric hole transport layers (HTL), poly(3, 4-ethylenedioxythiophene)-poly-(styrenesulfonate) (PEDOT:PSS) and poly-(triarylamine) (PTAA), that are known to provide different carrier transport characteristics in perovskite solar cells. In order to monitor the evolution of the perovskite charge carrier dynamics during the crystallization process, the so-formed CH3 NH3 PbI3 /HTL architectures were studied in situ by TAS at three different annealing temperatures, i.e., 90, 100 and 110 °C. It is revealed that the annealing time period required in order to achieve the optimum perovskite film quality in terms of the decay dynamics strongly depends on the annealing temperature, as well as, on the employed HTL. For both HTLs, the required period decreases as higher annealing temperature is used, while, for the more hydrophobic PTAA polymer, longer annealing periods were required in order to obtain the optimum charge carrier dynamics. The correlation of the TAS finding with the structural and morphological features of the perovskite films is analysed and provides useful insights on the charge extraction dynamics and recombination processes in perovskite optoelectronic devices.